Potential Adenostemma lavenia and Muntingia calabura Extracts to Inhibit Cyclooxygenase-2 Activity as a Therapeutic Strategy for Anti-inflammation: Experimental and Theoretical Studies - Bagaskoro Tuwalaid; Setyanto Tri Wahyudi; Dyah Iswantini (Universitas Gadjah Mada, 2022)
Continuous inflammation can cause new and more severe diseases, thus effective treatments are needed. One of the common inflammation treatments is given by reducing prostaglandins' production through the inhibition of COX-2 activity. This experiment aims to examine the potential application of plant extracts of Adenostemma lavenia and Muntingia calabura (Jamaica cherry) as anti-inflammatory agents in inhibiting COX-2 activity through in silico and in vitro assays. Molecular docking and molecular dynamics simulation were accomplished to evaluate the stability of the complex between COX-2 and ligands. The COX-2 inhibition was determined using the COX-2 Inhibitor Screening Assay KIT. Based on the docking results, the active compound from A. lavenia, ligand 1a,9b-dihydro-1H-cyclopropa[a]anthracene, has the lowest binding energy of -8.7 kcal/mol. In comparison, M. calabura contains 7-hydroxyflavone ligand with a Gibbs free energy of -9.1 kcal/mol. The molecular dynamics study demonstrates that COX-2 maintains its stability when forming interactions with selected compounds from all the tested extracts. The results of the COX-2 inhibition test showed that 96% EtOH extract of A. Lavenia at concentrations of 25 and 100 ppm had an inhibitory activity of 98%; meanwhile, 70% and 96% EtOH extracts of M. calabura at 1000 ppm concentration could inhibit COX-2 activity up to 100%. The results demonstrate that both plants show potential anti-inflammatory activity.